Autophagy in Inflammatory Diseases - Alexander J. S. Choi; Stefan W. Ryter (International Journal of Cell Biology)
Autophagy provides a mechanism for the turnover of cellular organelles and proteins through a lysosome-dependent degradation pathway. During starvation, autophagy exerts a homeostatic function that promotes cell survival by recycling metabolic precursors. Additionally, autophagy can interact with other vital processes such as programmed cell death, inflammation, and adaptive immune mechanisms, and thereby potentially influence disease pathogenesis. Macrophages deficient in autophagic proteins display enhanced caspase-1-dependent proinflammatory cytokine production and the activation of the inflammasome. Autophagy provides a functional role in infectious diseases and sepsis by promoting intracellular bacterial clearance. Mutations in autophagy-related genes, leading to loss of autophagic function, have been implicated in the pathogenesis of Crohn's disease. Furthermore, autophagy-dependent mechanisms have been proposed in the pathogenesis of several pulmonary diseases that involve inflammation, including cystic fibrosis and pulmonary hypertension. Strategies aimed at modulating autophagy may lead to therapeutic interventions for diseases associated with inflammation.